2015
DOI: 10.1038/bjc.2014.632
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on changes in quality of life among breast cancer survivors treated with breast-conserving surgery and radiotherapy

Abstract: Background:The purpose of the study was to determine the impact of young age on health-related quality of life (HRQoL) by comparing HRQoL of younger and older breast cancer patients, corrected for confounding, and of young patients and a general Dutch population.Methods:The population consisted of breast cancer survivors (stage 0-III) after breast-conserving surgery and radiotherapy. Health-related quality of life was prospectively assessed using the EORTC QLQ-C30 and QLQ-BR23 questionnaires. The association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 36 publications
10
32
2
2
Order By: Relevance
“…The negative association of age with acute RT-induced fatigue is consistent with another prospective study that suggested significant worsening of a constellation of RTinduced symptoms during RT for younger patients (6). Other studies have demonstrated that younger patients are more likely to experience fatigue and other psychosocial issues, likely because of a greater fear of a cancer diagnosis (1,43,44). However, on multivariate analysis controlling for anxiety, sadness, and psychiatric/pain-related comorbidity, younger age remained a significant predictor in our analysis.…”
Section: Discussionsupporting
confidence: 83%
“…The negative association of age with acute RT-induced fatigue is consistent with another prospective study that suggested significant worsening of a constellation of RTinduced symptoms during RT for younger patients (6). Other studies have demonstrated that younger patients are more likely to experience fatigue and other psychosocial issues, likely because of a greater fear of a cancer diagnosis (1,43,44). However, on multivariate analysis controlling for anxiety, sadness, and psychiatric/pain-related comorbidity, younger age remained a significant predictor in our analysis.…”
Section: Discussionsupporting
confidence: 83%
“…The age at diagnosis, therapeutic modality, as well as therapeutic sequelae all contribute to a breast cancer patient's QoL changes 11,15 . In this study we analyzed QoL of 170 early stage breast cancer female patients surgically treated, before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been observed that there was an improvement in the perceived QoL in all domains regardless of therapeutic modality. Bantema-Joppe et al 11 studied the influence of age on breast cancer patients' QoL after radiotherapy. The average follow-up time was 34 months (range 6-70 months), and results were compared to age-matched controls in the general population in Holland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort study from the Netherlands demonstrated that healthrelated quality of life (which includes the role functioning, emotional and cognitive functioning, fatigue, and pain) in the first year after BCS and radiotherapy is more strongly affected in young breast cancer survivors than in older patients, but improves over time 144 .…”
Section: Psychological and Social Burden Of Breast Cancer In Young Sumentioning
confidence: 99%